Short Communication: Prevalence of Listeria monocytogenes in Raw Milk of Healthy Sheep and Goats - Fatemeh Sepahvand; Ehsan Rashidian; Amin Jaydari; Heidar Rahimi (Veterinary Medicine International)
Listeria monocytogenes, one of the most important bacterial pathogens transmitted through milk, causes listeriosis in humans and animals. This study aimed to investigate the prevalence of L. monocytogenes in raw milk of healthy sheep and goats in the west of Iran (Lorestan Province) by touchdown PCR (TD-PCR). Listeria spp. were found in milk samples taken from 21 sheep (29.16%) and 3 goats (10.71%) whereas L. monocytogenes was isolated from milk samples taken from 4 sheep (5.55%) and 1 goat (3.75%). The results showed that there was a significant difference between sheep and goats in the prevalence of Listeria spp. in their raw milk (p<0.05), but no significant difference was observed between them in the prevalence of L. monocytogenes. The study findings suggested that the raw milk of healthy sheep and goats was infected with L. monocytogenes and warned of the risk of human infection with listeriosis following consumption of raw and unpasteurized milk.